Basaloid Squamous Cell Carcinoma of the Sigmoid Colon. Issue 3 (April 2015) - Samo, Salih; Sherid, Muhammed; Liu, Kevin; Kia, Leila; Elliott, Glynn J.
Abstract : N/A: Basaloid squamous cell carcinoma (BSCC) of the colon is rarely found proximal to the anal canal. We report a case of an 81‐year‐old woman who was diagnosed with squamous cell carcinoma (SCC) of the lung without metastasis and BSCC of the sigmoid with differing histologic findings suggesting that these tumors were separate primary neoplasms. SCC of the colon has a dismal prognosis. Surgery is the primary method of treatment when feasible, in addition to chemotherapeutic agents.